<htm> Scolytinae (Coleoptera, Curculionidae) associados a diferentes fitofisionomias no Pantanal de Cáceres, Mato Grosso </htm> - Meurer, Eliandra; Battirola, Leandro D.; Colpani, Daniara; Dorval, Alberto; Marques, Marinêz Isaac (Acta Biológica Paranaense, 2013)
<htm> Scolytinae (Coleoptera, Curculionidae) associados a diferentes fitofisionomias no Pantanal de Cáceres, Mato Grosso </htm>